1995
DOI: 10.1099/13500872-141-10-2455
|View full text |Cite
|
Sign up to set email alerts
|

The role of alanine in the acute response of Giardia intestinalis to hypo-osmotic shock

Abstract: The effect of medium hypo-osmolality on cell volume and intracellular amino acid composition was studied in the protozoan parasite Giadia intestinalis. When G. intestinalis was exposed to hypotonic medium, it initially swelled by 40% of its original volume and then decreased its volume, thus demonstrating a regulatory volume decrease process (RVD). These processes were accompanied by a rapid release of intracellular neutral amino acids, especially alanine, but not by amino acids with net charges such as glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
(19 reference statements)
4
13
0
Order By: Relevance
“…Thus damage to the plasma membrane, as indicated by the progressive loss of ability to exclude the anionic voltage-sensitive dye DiBAC % (3) (Lloyd & Hayes, 1995), led to swelling of organisms and loss of the regulatory volume control process, described in fully functional organisms (Park et al, 1995). Sites known to be O # -inhibited in G. intestinalis include a (4Fe-4S) iron-sulphur cluster (Ellis et al, 1993) and redox-active thiols involved in volume regulation (Park et al, 1995). The fact that these effects could also be produced almost immediately by 60 µM H # O # suggests that exposure to inhibitory levels of O # results in accumulation of this partial reduction product.…”
Section: Discussionmentioning
confidence: 99%
“…Thus damage to the plasma membrane, as indicated by the progressive loss of ability to exclude the anionic voltage-sensitive dye DiBAC % (3) (Lloyd & Hayes, 1995), led to swelling of organisms and loss of the regulatory volume control process, described in fully functional organisms (Park et al, 1995). Sites known to be O # -inhibited in G. intestinalis include a (4Fe-4S) iron-sulphur cluster (Ellis et al, 1993) and redox-active thiols involved in volume regulation (Park et al, 1995). The fact that these effects could also be produced almost immediately by 60 µM H # O # suggests that exposure to inhibitory levels of O # results in accumulation of this partial reduction product.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on G. intestinalis has shown that thiol‐reactive agents (e.g. N ‐ethylmaleimide) decrease the capacity of this organism to undergo volume regulation as a response to hypo‐osmotic shock (Park et al. 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Protozoans (kinetoplastids, apicomplexans and early eukaryotes) can osmoregulate by changing the concentration of alanine (Burrows and Blum 1991;Cronkite et al 1993;Park et al 1995;Ehud et al 2013). They also employ efflux of ions and water from their contractile vacuoles and intracellular compartments (LeFurgey et al 2001;Grønlien et al 2002;Rohloff and Docampo 2008).…”
Section: Protozoamentioning
confidence: 96%